Effects of Temperature on Thermodynamic parameters and Carbon Nanotubes Growth Rate on Aluminum Electrode in Electrochemical deposition Process - Rasheed, A. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The optimum process conditions of the electrochemical deposition of carbon nanotubes (CNT) have been established by using developed, cheap and simple system. It has been found that temperature affects on the rate, purity and the yield of CNT obtained in this process. The electrochemical behavior of CNT deposition, kinetic and thermodynamic parameters were also discussed.